2021
DOI: 10.1002/mgg3.1702
|View full text |Cite
|
Sign up to set email alerts
|

Preparing genomic revolution: Attitudes, clinical practice, and training needs in delivering genetic counseling in primary care in Hong Kong and Shenzhen, China

Abstract: Purpose The aim was to evaluate knowledge, attitudes, and clinical practice concerning medical genetics, genetic testing, and counseling among primary care physicians (PCPs) in Hong Kong and Shenzhen, China. Methods The University of Hong Kong (HKU), HKU‐Shenzhen Hospital, and Shenzhen Health Capacity Building and Continuing Education Center invited PCPs from Hong Kong and Shenzhen to participate in an online survey. Results The survey was completed by 151 PCPs and 258 PCPs from Hong Kong and Shenzhen, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…According to the National Organization for Rare Disorders (NORD) survey 2019, almost half of the patients and carers identified limited medical specialization to be a major barrier to delays in RD diagnosis (127). Previous studies have shown that many primary care physicians profess low confidence in their skillsets in managing patients with genetic-related issues and in using genetic information to make clinical decisions (128)(129)(130)(131). Primary care physicians have identified lack of knowledge and training opportunities to be the major barriers to genomic medicine in primary care (128,131,132).…”
Section: Future Directions Of Rdsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the National Organization for Rare Disorders (NORD) survey 2019, almost half of the patients and carers identified limited medical specialization to be a major barrier to delays in RD diagnosis (127). Previous studies have shown that many primary care physicians profess low confidence in their skillsets in managing patients with genetic-related issues and in using genetic information to make clinical decisions (128)(129)(130)(131). Primary care physicians have identified lack of knowledge and training opportunities to be the major barriers to genomic medicine in primary care (128,131,132).…”
Section: Future Directions Of Rdsmentioning
confidence: 99%
“…Previous studies have shown that many primary care physicians profess low confidence in their skillsets in managing patients with genetic-related issues and in using genetic information to make clinical decisions (128)(129)(130)(131). Primary care physicians have identified lack of knowledge and training opportunities to be the major barriers to genomic medicine in primary care (128,131,132). Emphasis on further education and training in genomic medicine among medical specialists should be prioritized in order to improve RD diagnosis and management.…”
Section: Future Directions Of Rdsmentioning
confidence: 99%
“…Of the 62 final articles included, 36 studies were quantitative studies,27–62 13 were qualitative studies,3 63–74 9 were randomised controlled trials75–83 and 4 were mixed-methods study70 84–86 (online supplemental table 5). The selected studies were conducted in USA (n=20), UK (n=19), Canada (n=11), Australia (n=6), Asia (n=4), New Zealand (n=1) and South Africa (n=1).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 11 studies, 7 studies found that GPs leaned towards having a minor role that focuses more on traditional genetic tasks of identifying, referring and providing psychological support rather than assessing and explaining genetic risks, benefits and limitations 28 31 38 51 56 60 86. Two studies found that less than 25% of the 1168 GPs surveyed were willing to discuss genetic testing,60 and 70% of the 271 GPs did not perceive ordering genetic tests or discussing about testing implications as part of their job scope 56.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation